Non-accidental harms (`abuse`) in athletes with impairment (`para athletes`): a state-of-the-art review - Tuakli-Wosornu, Y. A.; Sun, Q.; Gentry, M.; Ona Ayala, K. E.; Doolan, F. C.; Ottesen, T. D.; Caldwell, B.; Naushad, N.; Huang, P.; Kirby, S. (British Journal of Sports Medicine, 2020)
Para athletes reap significant health benefits from sport but are vulnerable to non-accidental harms. Little is known about the types and impacts of non-accidental harms Para athletes face. In this literature review, we summarise current knowledge and suggest priorities for future research related to non-accidental harms in Para athletes.